Study protocol: a dose-escalating, phase-2 study of oral lisdexamfetamine in adults with methamphetamine dependence - Ezard, Nadine (BMC Psychiatry, 2016)
BACKGROUND: The treatment of methamphetamine dependence is a continuing global health problem. Agonist type pharmacotherapies have been used successfully to treat opioid and nicotine dependence and are being studied for the treatment of methamphetamine dependence. One potential candidate is lisdexamfetamine, a pro-drug for dexamphetamine, which has a longer lasting therapeutic action with a lowered abuse potential. The purpose of this study is to determine the safety of lisdexamfetamine in this population at doses higher than those currently approved for attention deficit hyperactivity disorder or binge eating disorder. METHODS/DESIGN: This is a phase 2 dose escalation study of lisdexamfetamine for the treatment of methamphetamine dependence. Twenty individuals seeking treatment for methamphetamine dependence will be recruited at two Australian drug and alcohol services. All participants will undergo a single-blinded ascending-descending dose regime of 100 to 250 mg lisdexamfetamine, dispensed daily on site, over an 8-week period. Participants will be offered counselling as standard care. For the primary objectives the outcome variables will be adverse events monitoring, drug tolerability and regimen completion. Secondary outcomes will be changes in methamphetamine use, craving, withdrawal, severity of dependence, risk behaviour and other substance use. Medication acceptability, potential for non-prescription use, adherence and changes in neurocognition will also be measured. DISCUSSION: Determining the safety of lisdexamfetamine will enable further research to develop pharmacotherapies for the treatment of methamphetamine dependence. TRIAL REGISTRATION: Australian and New Zealand Clinical Trials Registry ACTRN12615000391572 Registered 28(th) April 2015.